Peran Earning Per Share Dalam Memediasi Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan - Rinny Meidiyustiani; Mia Laksmiwati; Triana Anggraeni; Wulan Dwi Antari (Politeknik Ganesha Medan, 2022)
This research is based to see the extent of the influence of the role of Earning Per Share in Mediating the Effect of Financial Performance on Firm Value. This PBV value is used to assess the price of the shares offered by the company, expensive or cheap, if the PBV value > 1, it is certain that the share price is expensive, and vice versa. . The sample was taken by purposive sampling by collecting company data on the IDX, namely plantation sector companies from 2015 to 2020. The sample obtained was 14 companies. The statistical method used to test the hypothesis is SEM-PLS (Structural Equation Model – Partial Least Square). The results of this study found that the ratio of profitability, solvency and activity had an effect on firm value, while liquidity had no effect on firm value. Meanwhile, EPS can only strengthen the influence of the solvency ratio on firm value.